A SIMPLE PROTOCOL FOR SOMATIC EMBRYOGENESIS INDUCTION OF IN VITRO SUGARCANE ( Saccharum officinarum. L) BY 2,4-D AND BAP - Widuri, Laily Ilman; Dewanti, Parawita; Sugiharto, Bambang (BIOVALENTIA: Biological Research Journal, 2016)
Induction of in vitro sugarcane through somatic embryogenesis technique influenced by addition of plant growth regulator. The objective of this research was to determine appropriate formulation medium for indirect somatic embryogenesis induction on two potential sugarcane SUT Event 02 and PS 881. This research carried out in three steps, callus induction, callus proliferation, and shoot regeneration. Explants taken from basal of in vitro plantlet one month SUT Event 02 and PS 881 resulted from shoot regeneration previously. Five different medium formulas applied for callus induction and one formula for proliferation and shoot regeneration. Research using completely randomized design (CRD) factorial with five different formulation induction mediums. The result showed that the best respond of indirect somatic embryogenesis on SUT Event 02 and PS 881 was medium containing Â 3 mgL-1of Â 2,4-D.